Children consuming cassava as a staple food are at risk for inadequate zinc, iron, and vitamin A intake - Gegios, A.; Amthor, R.; Maziya-Dixon, B.B.; Egesi, Chiedozie N.; Mallowa, S.; Nungo, R.; Gichuki, S.; Mbanaso, A.; Manary, M.J. (Springer, 2010)
Cassava contains little zinc, iron, and β-carotene, yet it is the primary staple crop of over 250 million Africans. This study used a 24-hour dietary recall to test the hypothesis that among healthy children aged 2–5 years in Nigeria and Kenya, cassava’s contribution to the childrens’ daily diets is inversely related to intakes of zinc, iron, and vitamin A. Dietary and demographic data and anthropometric measurements were collected from 449 Kenyan and 793 Nigerian children. Among Kenyan children 89% derived at least 25% of their dietary energy from cassava, while among the Nigerian children 31% derived at least 25% of energy from cassava. Spearman’s correlation coefficient between the fraction of dietary energy obtained from cassava and vitamin A intake was r = −0.15, P < 0.0001, zinc intake was r = −0.11, P < 0.0001 and iron intake was r = −0.36, P < 0.0001. In Kenya, 59% of children consumed adequate vitamin A, 22% iron, and 31% zinc. In Nigeria, 17% of children had adequate intake of vitamin A, 57% iron, and 41% zinc. Consumption of cassava is a risk factor for inadequate vitamin A, zinc and/or iron intake.